Effects of Practice and Experience on the Arcuate Fasciculus: Comparing Singers, Instrumentalists, and Non-Musicians - Halwani, Gus F.; Loui, Psyche; Rueber, Theo; Schlaug, Gottfried (Frontiers in Psychology, 2011)
Structure and function of the human brain are affected by training in both linguistic and musical domains. Individuals with intensive vocal musical training provide a useful model for investigating neural adaptations of learning in the vocal-motor domain and can be compared with learning in a more general musical domain. Here we confirm general differences in macrostructure (tract volume) and microstructure (fractional anisotropy (FA)) of the arcuate fasciculus (AF), a prominent white-matter tract connecting temporal and frontal brain regions, between singers, instrumentalists, and non-musicians. Both groups of musicians differed from non-musicians in having larger tract volume and higher FA values of the right and left AF. The AF was then subdivided in a dorsal (superior) branch connecting the superior temporal gyrus and the inferior frontal gyrus (STG<–>IFG), and ventral (inferior) branch connecting the middle temporal gyrus and the inferior frontal gyrus (MTG<–>IFG). Relative to instrumental musicians, singers had a larger tract volume but lower FA values in the left dorsal AF (STG<–>IFG), and a similar trend in the left ventral AF (MTG<–>IFG). This between-group comparison controls for the general effects of musical training, although FA was still higher in singers compared to non-musicians. Both musician groups had higher tract volumes in the right dorsal and ventral tracts compared to non-musicians, but did not show a significant difference between each other. Furthermore, in the singers’ group, FA in the left dorsal branch of the AF was inversely correlated with the number of years of participants’ vocal training. Our findings suggest that long-term vocal-motor training might lead to an increase in volume and microstructural complexity of specific white matter tracts connecting regions that are fundamental to sound perception, production, and its feedforward and feedback control which can be differentiated from a more general musician effect.